Comparative cutting ability and cleaning efficiency of four nickel-titanium rotary endodontic instruments (Research, Society and Development, 2023)
The aim of this investigation was to evaluate the cutting capacity of 4 endodontic instruments of the Ni-Ti rotary system was evaluated according to the number of uses in 20 blocks with simulated phenolic resin channels (Baquelite®) and 750 of curvature, being tested 20 files of different brands divided into 4 groups: GA–Twisted File® files (25/12, 25/10, 25/08, 25/06, 25/04) (n=5); GB- LimasBioRaCe®(08/25, 05/15, 04/25, 06/25, 04/35 and 04/40) (n=6); GC–Files Mtwo® (10/04, 15/05, 20/06 and 25/06) (n=4) and GD–Limes EndoWave® (35/08, 30/06, 25/ .06, 06/20 and 02/15) (n=5). Files and blocks were washed before use. The blocks were dried with absorbent paper and oven at 1000C for 2 h, weighed before and after on a precision scale (SA–210, Quimes). In both groups, an X-Smart® motor (Dentsply/Maillefer, Switzerland) was used for instrumentation with a speed of 300rpm and programmed torque control and 1.6N of force. Initially, the canal was irrigated with 5mL of 1% sodium hypochlorite (Officinalis®) and instrumentation auxiliary chemical substance Endo PTC® cream neutralized by 1% sodium hypochlorite and irrigation/aspiration of the canal with 5mL of hypochlorite solution 1% sodium. The Mtwo® instrument promoted greater resin removal, that is, greater efficiency in cutting the simulated canal followed by the BioRaCe® file, EndoWave® in the five different uses, while the TwistedFile® instrument removed less material. The substrate based on phenolic resin showed stability in the wear tests with respect to weight loss of the blocks.